A TRANSLATION EQUIVALENCE ANALYSIS OF ABSTRACT TRANSLATION IN FACULTY OF COMPUTER SCIENCE UNIVERSITY OF BANTEN JAYA 2019 - Artica Rizza Anjani; Sisca Wulansari Saputri; Aa Qona’atun (Journal of English Language Teaching and Literature (JELTL), 2021)
The research is content analysis which explores the using of translation equivalences applied in Faculty of Computer Science. Considering that the Faculty of Computer Science indirectly and unconsciously often carry out the process of translation in daily activities in the programming language used. The research thus aims to provide how is translation equivalence and what is the dominant translation equivalence used in translation of abstract internship report in Faculty of Computer Science 7th semester in Banten Jaya University 2019. The data conducted from 3 sections of collecting data which taken randomly from 20 abstract translations of internship report, divided into 10 abstracts from Information System Program and 10 abstracts from Information Engineering Program. The Mona Baker’s theories applied in the order to identified and classify the translation equivalences. Furthermore, Miles and Huberman method also used to analyzed the abstract of internship report to find out the first question. In the other hand a formula by Butler used to find out the second question. As the result of this research, the most dominant translation equivalence used is Above Word Level Equivalence with 35 cases (28.69%), which followed by Pragmatic Equivalence with 30 cases (24.59%), Word Level Equivalence with 26 cases (21.31%), Grammatical Equivalence with 16 cases (13.11%), and Textual Equivalence with 15 cases (12.30%).The research concludes that the translation equivalence in translations process depend on the translator point of view.